Humor com dessabor: uma análise das tiras da Mafalda no contexto escolar - Gonçalves, Jessica de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research turns one's eyes to the statements of some pre-school students of the Adventist College in Tupa on the comic strips of Mafalda. Given the occurrence of these in school activities, textbooks and reviews, these students presented several speeches about the strips and about the character Mafalda during the Portuguese language classes taught by the researcher of this study. Many said they did not become interested in reading these and did not understand the criticism and the effects of humor contained therein. The aim of this study is to investigate the factors involved in the act of reading this genre that carry certain disinterest and misunderstanding when in school / evaluative context. We discuss for this the conceptions of humor and gender strip submitted by students in reading activities proposed in the form of case study. It reflects also on the approach of the strip as a discursive genre in school / evaluative context, from the analysis of the teaching materials used by the studied group and the students' answers to the relations of humor and criticism present in the genre. To this end there was a case study that proposed reading activities with strips from the work Ten years with Mafalda and worked in schools, in a class of third year high school students in a college of a private school in Tupa / SP, the Adventist College. The activities were held in the Portuguese language classes, in and out of evaluative context. Here are used as theoretical apparatus of the study gender concepts / statement, act, ideology / ideological and subject sign, as designed by the Circle of Bakhtin / Medviedév / Volochínov. It is further proposed a methodology based on the chronotope of ideas, exotopy, otherness and voice discussed by the Russian circle. The categories of analysis proposals arise from the very method of conducting the case study. In strip Mafalda, seen as an ideological sign, ascertain the views of many speeches, in which ...

Esta pesquisa volve os olhares para os enunciados de alguns alunos pré-vestibulandos do Colégio Adventista de Tupã sobre as tiras da Mafalda. Diante da ocorrência dessas em atividades escolares, livros didáticos e avaliações, estes alunos apresentaram discursos diversos sobre as tiras e sobre a própria personagem Mafalda durante as aulas de língua portuguesa ministradas pela pesquisadora deste trabalho. Muitos afirmaram não se interessarem pela leitura destas e não compreenderem as críticas e os efeitos de humor ali contidos. O objetivo geral deste estudo é investigar os fatores envolvidos no ato de ler tal gênero que acarretam certo desinteresse e incompreensão, quando em contexto escolar/avaliativo. Discutem-se para isso as concepções de humor e do gênero tira apresentadas pelos alunos nas atividades de leitura proposta em forma de estudo de caso. Reflete-se ainda sobre a abordagem da tira como gênero discursivo em contexto escolar/avaliativo, a partir da análise desta no material didático utilizado pelo grupo em estudo e das respostas dos alunos às relações de humor e crítica presentes no gênero. Com essa finalidade realizou-se um estudo de caso que propôs atividades de leitura de tiras retiradas da obra Dez anos com Mafalda e trabalhadas em contexto escolar, em uma turma do terceiro ano do Ensino Médio de um colégio da rede privada de ensino em Tupã/SP, o Colégio Adventista. As atividades foram realizadas nas aulas de língua portuguesa, dentro e fora de contexto avaliativo. Utilizam-se como aparato teórico deste estudo os conceitos de gênero/enunciado, ato, ideologia/signo ideológico e sujeito, conforme pensados pelo Círculo de Bakhtin/ Medviedév/ Volochínov. Propõe-se ainda uma metodologia fundamentada nas ideias de cronótopo, exotopia, alteridade e voz discutidas pelo círculo russo. As categorias de análise propostas surgem do próprio método de realização do estudo de caso. Na tira da Mafalda...
Keywords: Educação; Gêneros literários; Escolas; Histórias em quadrinhos; Education